Ni(II) and Cu(II) complexes of pyridine-carboxamide Schiff base: Synthesis, characterization, and antioxidant activities evaluation - Turan, Nevin; Olcay Aydin; Buldurun, Kenan (Hacettepe Üniversitesi, 2025)
This research introduces two novel Schiff base complexes: [LNi(H2O)2]H2O and [LCu]3H2O, where L represents (E)-2-(5-bromo-2-hidroksibenzilidenamino)-6-metil-4,5,6,7-tetrahidrotiyeno[2,3-c]piridin-3-karboksamid. These complexes were synthesized by reacting of Schiff base ligand (L) containing ON donor atoms with an equimolar amount of NiCl2·6H2O and Cu(NO3)2·3H2O salts. The compounds were extensively characterized using various analytical and spectroscopic techniques, including elemental analysis, FT-IR, 1H-NMR, 13C-NMR, UV-Vis spectroscopy, mass spectrometry, magnetic susceptibility measurements, molar conductivity, and thermogravimetric analysis. Additionally, the antioxidant properties of both the ligand and complexes were evaluated in vitro using three methods: DPPH free radical scavenging activity, ABTS+ cation radical scavenging activity, and CUPRAC reducing power. From the analytical data, it was observed that the Ni(II) complex has an octahedral structure and the Cu(II) complex has a square planar structure. The antioxidant activity results indicated that some of the complex compounds demonstrated superior antioxidant effects compared to the Schiff base ligand.
BAP-22-FEF-4902-08
Keywords: Bioinorganic Chemistry; Biyoinorganik Kimya; Transition Metal Chemistry; Geçis Metal Kimyasi